2015
DOI: 10.1111/jedm.12081
|View full text |Cite
|
Sign up to set email alerts
|

Criterion‐Related Validity: Assessing the Value of Subscores

Abstract: Criterion-related profile analysis (CPA) Lately, there has been much interest in subscores, because they can potentially provide diagnostically useful information. A subscore refers to a score on one test in a test battery or one section of a single test. A score profile x p = (X 1 , X 2 , . . . , X V ) is the vector of V subscores for person p, where p = 1, . . . , P and v = 1, . . . , V, and the total for person p is a sum of the subscores X p = v X pv . Recent literature shows at least three lines of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…To address this question, Biancarosa et al. () employed a logistic regression analysis of incorrect answer profiles (Davison, Davenport, Chang, Vue, & Su, ). For purposes of this analysis, it was recognized that students could be scored as incorrect for one of three reasons: a paraphrase response, a lateral connection response, or not completing the item.…”
Section: Multiple‐choice Online Causal Comprehension Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this question, Biancarosa et al. () employed a logistic regression analysis of incorrect answer profiles (Davison, Davenport, Chang, Vue, & Su, ). For purposes of this analysis, it was recognized that students could be scored as incorrect for one of three reasons: a paraphrase response, a lateral connection response, or not completing the item.…”
Section: Multiple‐choice Online Causal Comprehension Assessmentmentioning
confidence: 99%
“…Having shown that incorrect answer scores can be reliable, we then turned to the question of whether those scores provide additional information not available from a simple NC score. To address this question, Biancarosa et al (2019) employed a logistic regression analysis of incorrect answer profiles (Davison, Davenport, Chang, Vue, & Su, 2015). For purposes of this analysis, it was recognized that students could be scored as incorrect for one of three reasons: a paraphrase response, a lateral connection response, or not completing the item.…”
Section: Do Incorrect Responses Matter?mentioning
confidence: 99%
“…conjunction with other variables, such as demographics, if subsequent investigative analysis is desired. According to Davison, Davenport, Chang, Vue, and Su (2015), the usefulness of a scoring methodology (such as aPRIDIT provides for each individual) is increased if the scores can be used for predicting an external criterion. By contrast, Kohonen classification is graphical in nature (Brockett et al, 1998), and would be hard to incorporate into other numerical statistical analysis.…”
Section: Comparison With Kohonen Self-organizing Feature Mapsmentioning
confidence: 99%
“…Some studies have evaluated the added value of subscores based on reliability (Brennan, 2011(Brennan, , 2015Feinberg & Wainer, 2014;Haberman, 2008;Haberman et al, 2009;Sinharay, 2014). Other studies have focused on validity of subscores (Davison, Davenport, Chang, Vue, & Su, 2015;Haladyna & Kramer, 2004). Haberman (2008) proposed PRMSE, an index indicating the added value of subscores over the total scores.…”
Section: Subscore Reportingmentioning
confidence: 99%
“…The author applied the suggested method to data from several operational tests and found that the added value of subscores with respect to classification was very similar to their added value using Haberman's approach, except at extreme cut scores. Davison et al (2015) assessed the value of subscores in predicting an external criteria. They conducted a criterion-related profile analysis (CPA) to determine whether subscores account for more criterion variance than does the total score.…”
Section: Subscore Reportingmentioning
confidence: 99%